ANALYSIS OF INSTRUCTIONAL MATERIAL BASED ON ENGLISH FOR SPECIFIC PURPOSES ON THE NEEDS OF MANAGEMENT STUDENTS AT STIE TRI DHARMA NUSANTARA - Syamsinar Syamsinar; Marwah Juwita Yusuf (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2019)
The difficulty of finding textbooks that fit the needs of students in Management studies makes researchers interested in analysing English material for teaching at the tertiary level. Needs analysis is the first step in developing and improving teaching materials and improving learning activities. In addition, needs analysis is very effective in evaluating students' needs in relation to English for academic, specific, and general purpose. Musdalifa and Syarifuddin (2017) state that needs analysis is very important and as a guideline for designing syllabi, subject matter, and class activities. This study is entitled "Analysis of Instructional Material Based on English for Specific Purposes on the Needs of Management Students at STIE Tri Dharma Nusantara." Participants in the study were 56 students in the Management study program, 2 English lecturers, 1 Management lecturer and the Head of the Management department. This research method is a descriptive qualitative research. The instruments used in data collection are participant observation, questionnaire, and interview. Data were analysed based on Miles and Huberman's model (2012: 129-136) which included reduction data, display data, and conclusion. The results of this study are the topic of English II material based on the analysis of the needs of students majoring in Management based on English for Specific Purpose. Topics of the material are Asking and Giving Direction, Describing Job, Application Letters and Curriculum Vitae, Job Interviews, Writing E-mails, Management Technical Terms, Pronunciation, Talking to A Foreigner, Business Proposals, and Presentation Skills. Furthermore, the skills most needed by students in Management study programs are speaking skills, followed by listening, reading and writing skills. The topic of the material will be arranged into a syllabus and instructional materials in the form of English language modules II. Therefore, this study pays attention to aspects of English for specific purposes in determining topics and formulating teaching materials in order to be able to improve learning activities. Not only English in general but also English based on the needs of management majors both at the academic level and in the world of work in the future.